Analisis Perbandingan Efisiensi Kinerja Bank Muamalat Indonesia Sebelum Dan Selama Pandemi Covid-19 Dengan Menggunakan Metode Data Envelopment Analysis (DEA) - Muflihah, Hani (ITB AAS INDONESIA Surakarta, 2024)
The world was faced with the phenomenon of the emergence of the co-19 pandemic in early 2020 which also hit Indonesia. This has caused several economic sectors in Indonesia to be affected, one of which is the Islamic banking sector. The impact felt by Islamic banking is a decrease in financial performance which will interfere with the efficiency of the institution's performance. The type of research in this study is quantitative using the Data Envelopment Analysis (DEA) method, with input variables (Total Assets, Labor Costs, and DPK) and output variables (Financing and Operating Income). By using quarterly data sourced the financial statements of Bank Muamalat Indonesia from the period 2018-2022. The results obtained from this study indicate that the average performance efficiency of Bank Muamalat Indonesia before the covid-19 pandemic was 87.63% and the average during the covid-19 pandemic was 71.38%, meaning that the performance efficiency of Bank Muamalat Indonesia during the covid-19 pandemic decreased by 16.27% from the period before covid-19. From the results of the paired sample t test, it also shows a significant value of 0.004